Prognostic significance of miR-1268a expression and its beneficial effects for post-operative adjuvant transarterial chemoembolization in hepatocellular carcinoma - Lu, Yun-Long (Sci Rep, 2016)
Our recent investigation has shown that the variables of microRNA-1268a may involve in hepatocellular carcinoma (HCC) tumorigenesis. Here, we attempted to identify the prognostic significance of microRNA-1268a expression in tumor tissues by a retrospective analysis in 411 patients with HCC, and analyze its effects on post-operative adjuvant transarterial chemoembolization (TACE) improving HCC prognosis. All cases received tumor resection or tumor resection plus post-operative adjuvant TACE as an initial treatment. Logistical regression analysis exhibited that microRNA-1268a expression was significantly correlated with tumor stage, tumor grade, tumor size, and microvessel density. Cox regression analysis showed that microRNA-1268a expression was an independent prognostic factor for HCC, and TACE treatment had no effects on prognosis of HCC patients with high microRNA-1268a expression. More intriguingly, TACE improved the prognosis of HCC patients with low microRNA-1268a expression. Functionally, overexpression of microRNA-1268a inhibited while its inhibitor enhanced doxorubicin-induced the death of cancer cells. These results suggest that microRNA-1268a may be an independent prognostic factor for HCC patients, and that decreasing microRNA-1268a expression may be beneficial for post-operative adjuvant TACE treatment in HCC.